此题答案:n(n+1)(n+2)(n+3)+1=(n+1)(n+2) * n(n+3)+1=(n^2+3n+2)(n^2+3n)+1=(n^2+3n)^2+2(n^2+3n)+1------------------展开=(n^2+3n+1)^2-----------配成完全平方以上答案为8*9*10*11+1 =(8^2+3*8+1)^2=89^2
第一个是1×(1+1)×(1+2)×(1+3)+1=[1×(1+3)+1]²
第二个也相同……
用n表示那么n×(n+1)×(n+2)×(n+3)+1=[n×(n+3)+1]²
第二个就是(3-2,3-1),(6-2,6-1)
那么规律是第n个数对是(3n-2,3n-1)
以此为例1.:1*2*3*4+1=(1*4+1)^2
2*3*4*5+1=(2*5+1)^2
以下略了
2.(1,2)(1+3,2+3) (1+3+3,2+3+3)……(1+9*3,2+9*3) 第10个
n(n+1)(n+2)(n+3)+1=n(n+3)(n²+3n+2)+1=n²(n²+3n+2)+3n(n²+3n+2)+1=n²(n²+3n+2)+3n(n²+3n+2)+2(n²+3n+2)-2(n²+3n+2)+1=(n²+3n+2)(n²+3n+2)-2(n²+3n+2)+1=[(n²+3n+2)²-1]=[(n+1)(n+2)-1]²
{(8*11)+1}*2